Planetary gear trains - Arnaudov, Kiril Borisov; Karaivanov, Dimitar Petkov (Boca Raton : Taylor & Francis, a CRC title, part of the Taylor & Francis imprint, a member of the Taylor & Francis Group, the academic division of T&F Informa, plc, 2019)
This book provides comprehensive information for various planetary gear trains, with practical applications and comprehensive references to technical articles. In the text's chapters, readers can find all the information needed for various types of gear trains, with illustrations and examples. The authors help gear designers to creatively understand the design of gears, as well as master the mechanical calculations needed. Planetary Gear Trains is the most comprehensive and up-to-date work available in this key technical area. The book reflects not only teaching, but also the practical experience of the authors. It was developed under the motto "From practice to practice".
OCLC-licensed vendor bibliographic record.
Keywords: Gearing, Planetary; Gearing, Planetary -- Design and construction; TECHNOLOGY & ENGINEERING / Mechanical; TECHNOLOGY / Industrial Design / General; TECHNOLOGY / Engineering / Mechanical